Regional Economic Outlook, April 2018, Western Hemisphere Department : Seizing the Momentum. (Regional Economic Outlook, 2018)
The world economy and global trade are experiencing a broad-based cyclical upswing. Since October 2017, global growth outcomes and the outlook for 2018-19 have improved across all regions, reinforced by the expected positive near-term spillovers from tax policy changes in the United States. Accommodative global financial conditions, despite some tightening and market volatility in early February 2018, have been providing support to economic recovery. Higher commodity prices are contributing to an improved outlook for commodity exporters. The US and Canadian economies posted solid gains in 2017 and are expected to grow above potential in the near term. Despite the improved near-term outlook, however, medium-term prospects are tilted downwards. Growth prospects for advanced economies are subdued and many emerging market and developing economies are projected to grow in per capita terms more slowly than advanced economies, raising concerns about income convergence. While risks appear broadly balanced in the near term, they skew to the downside over the medium term, including a possible sharp tightening of financial conditions, waning popular support for global economic integration, growing trade tensions and risks of a shift toward protectionist policies, and geopolitical strains.